The differential expression of alternatively polyadenylated transcripts is a common stress-induced response mechanism that modulates mammalian mRNA expression in a quantitative and qualitative fashion - Hollerer, Ina; Curk, Tomaz; Haase, Bettina; Benes, Vladimir; Hauer, Christian; Neu-Yilik, Gabriele; Bhuvanagiri, Madhuri; Hentze, Matthias W.; Kulozik, Andreas (RNA, 2016)
Stress adaptation plays a pivotal role in biological processes and requires tight regulation of gene expression. In this study, we explored the effect of cellular stress on mRNA polyadenylation and investigated the implications of regulated polyadenylation site usage on mammalian gene expression. High-confidence polyadenylation site mapping combined with global pre-mRNA and mRNA expression profiling revealed that stress induces an accumulation of genes with differentially expressed polyadenylated mRNA isoforms in human cells. Specifically, stress provokes a global trend in polyadenylation site usage toward decreased utilization of promoter-proximal poly(A) sites in introns or ORFs and increased utilization of promoter-distal polyadenylation sites in intergenic regions. This extensively affects gene expression beyond regulating mRNA abundance by changing mRNA length and by altering the configuration of open reading frames. Our study highlights the impact of post-transcriptional mechanisms on stress-dependent gene regulation and reveals the differential expression of alternatively polyadenylated transcripts as a common stress-induced mechanism in mammalian cells.
Gesehen am 20.05.2020